Frost heaving strain monitoring for lining structure in extreme cold and high-altitude area with FBG strain sensors. (15th June 2022) - Li, Chuan; Yang, Lubing; Luo, Chuan; Liu, Hao; Wan, Xiaorong
Abstract: Due to the extreme temperature with significant variation in the alpine region, the tunnels in this area are subjected to intense freeze–thaw cycles and frost heaves, which leads to the cracking of the second lining structure. We propose an approach to monitor the frost heaving strain of the second lining and simultaneously measure the thermal strain and applied stress strain of the structure. The Fiber Bragg Grating (FBG) strain sensors are installed on the structure surface to measure the strains caused by the thermal strain and loaded stress. Meanwhile, one FBG temperature sensor is installed on the structure surface to measure the local temperature. Then, the structure thermal strain and applied stress strain are simultaneously measured based on the sensitivity difference for temperature and strain response of the above two measurement methods. The proposed approach is implemented in an alpine region tunnel. The results show that the local temperature is inversely proportional to the total strain and the thermal apparent strain of the second lining. The applied stress–strain of the lining fluctuates in a small range, and the thermal strain from the daily temperature difference incremental demodulation is very close to the daily strain difference. Therefore, the main cause of lining frost damage is the thermal strain due to the local temperature variation, and there is no frost heave occurred in the surrounding rock. Thus, the method is offered to monitor the freeze–thaw cycles and freeze-swelling effects in the extreme cold and high-altitude tunnels. Highlights: A fiber Grating monitoring model for simultaneous measurement about thermal apparent-strain and applied stress–strain of concrete structure is designed. The model is applied in high-cold and high-altitude tunnel to monitor the thermal apparent-strain and applied stress–strain of the lining for frost damage researching. According to the monitoring results, the surrounding rock had not undergone frost heave, the strain of the lining was mainly caused by the temperature load. Considering the thermal strain of the lining structure in the process of monitoring the lining strain can effectively analyze the degree of frost heave of surrounding rock and lining, respectively.